Women’s Empowerment and Child Stunting in India: An Investigation - Kumar, Rishi; Lakhtakia, Supriya (Journal of Population and Social Studies [JPSS], 2020)
Child stunting is associated with substantial impediments to human development and loss in human capital. An important factor contributing to the prevalence of stunting, a manifestation of malnutrition among children, is believed to be women’s lack of empowerment. This paper, therefore, aims to describe the trends and variations in child stunting in India using data from the National Family and Health Survey. This study also seeks to find the factors associated with child stunting, with particular focus on the influence of women’s empowerment. We analyzed stunting across various socioeconomic groups, and applied chi-square tests and logistic regression modeling to determine whether any significant association existed between the different dimensions of women’s empowerment and child stunting. We found that the financial autonomy of women is one of the factors which is associated with a reduction in the odds of being a child stunted. Other reasons that decrease the odds of child stunting are maternal health, measured by body mass index, and the number of antenatal visits during pregnancy. Women’s empowerment can, therefore, play an essential role in improving child nutrition.